BioInfograph: An Online Tool to Design and Display Multi-Panel Scientific Figure Interactively - Li, Kejie; Hurt, Jessica; Whelan, Christopher D.; Challa, Ravi; Lin, Dongdong; Zhang, Baohong (Frontiers in Genetics, 2022)
Many fit-for-purpose bioinformatics tools generate plots to interpret complex biological data and illustrate findings. However, assembling individual plots in different formats from various sources into one high-resolution figure in desired layout requires mastery of commercial tools or even programming skills. In addition, it is a time-consuming and sometimes frustrating process even for a computational savvy scientist, who frequently takes a trial-n-error iterative approach to get satisfactory result. To address the challenge, we developed bioInfograph, a web-based tool that allows user to interactively arrange high-resolution images in diversified formats, mainly SVG to produce one multi-panel publication-quality composite figure in both PDF and HTML formats in a user-friendly manner, requiring no programming skills. It solves stylesheet conflicts of co-existing SVG plots, integrates a rich-text editor, and allows creative design by providing advanced functionalities like image transparency, controlled vertical stacking of plots, versatile image formats, and layout templates. To highlight, the sharable interactive HTML output with zoom in function is a unique feature not seen in any other similar tools. In the end, we make the online tool publicly available at https://baohongz.github.io/bioInfograph while releasing the source code at https://github.com/baohongz/bioInfograph under MIT open-source license.